1993
DOI: 10.1002/mrm.1910300314
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of perfusion in the isolated rat heart using spin inversion of arterial water

Abstract: Measurement of regional myocardial perfusion is important for the diagnosis and treatment of coronary artery disease. Currently used methods for the measurement of myocardial tissue perfusion are either invasive or not quantitative. Here, we demonstrate a technique for the measurement of myocardial perfusion using magnetic resonance imaging (MRI) with spin tagging of arterial water. In addition, it is shown that changes in perfusion can be quantitated by measuring changes in tissue T1. Perfusion images are obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 9 publications
1
70
0
Order By: Relevance
“…In several studies attention was paid to the validation of the ASL measurements. For instance, brain perfusion obtained with T 1app sequences was compared with PET results (17) and myocardial perfusion with radioactive microsphere measurements (11,14). The ASL data were found to be in good agreement with the established standards.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In several studies attention was paid to the validation of the ASL measurements. For instance, brain perfusion obtained with T 1app sequences was compared with PET results (17) and myocardial perfusion with radioactive microsphere measurements (11,14). The ASL data were found to be in good agreement with the established standards.…”
mentioning
confidence: 67%
“…Second, perfusion maps are generated at excellent temporal and spatial resolutions. Since their introduction by Detre et al (1) and Williams et al (2) in 1992, various ASL protocols, and in particular pulsed ones (3,4), have been increasingly used and have been shown to measure perfusion mainly in the brain (1,3,(5)(6)(7) and also in other organs such as kidney (8 -10), heart (11)(12)(13)(14), and lungs (15,16). In several studies attention was paid to the validation of the ASL measurements.…”
mentioning
confidence: 99%
“…In cerebral studies, fast exchange is hindered by the blood-brain barrier, and high cerebral blood flows are underestimated by ASL. Experimental studies conducted on in vitro perfused hearts have demonstrated that the fast exchange condition was not an issue in organs other than the brain (104). Finite and non-instantaneous exchange times are to be taken into account when blood and tissue T 1 s are different, but the correction to be introduced is minor (68).…”
Section: Nmr Determination Of Skeletal Muscle Perfusion: a Key-role Fmentioning
confidence: 99%
“…There exist qualitative 11,12 and quantitative [13][14][15][16][17] non-contrastagent perfusion imaging techniques. Most of the latter techniques work with active labeling of the inflowing spins.…”
Section: Development Of Perfusion Imagingmentioning
confidence: 99%